Orthodontics related mouth breathing patient: literature review (Research, Society and Development, 2022)
This work aims to study the relationship between a mouth breathing patient and orthodontic treatment through a literature review. Breathing is essential for the functioning of the system, which malfunctions throughout the human body and diverse systems. Correct breathing brings benefits to the body, in digestion, in the body, even in the accumulation of organic organs, in the rebalancing of organic functions and in the fight against anxiety and obesity. The most common differences of people who are mouth breathers are changes in craniofacial and also dental structure, changes in phonoarticular, corporeal, behavioral and oral function. The multidisciplinary treatment must be greater and treated as soon as possible, the earlier the recognition and treatment of oral obstructions, speech therapy and orthodontics, the better the patient's final result.